2020
DOI: 10.1002/ccr3.2823
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual dermoid cyst in an infant: A case report and review of the literature

Abstract: Dermoid cysts usually occur later in the second decade of life; we present the approach of an unusual case of an infant who presented a cyst within the oral cavity, which is important because it can be confused with other pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
5
0
6
Order By: Relevance
“…7% of dermoid cysts occur in the head and neck, while 1.6% occurs in the mouth [15]. There is no significant gender predilection however a review of literature by Vélez-Crus, et al noted a high incidence among men after 30 years (84.61%) and only 15.38% among women [19]. A higher male predominance (3:1) was also noted by Longo, et al in his review of 16 dermoid cyst cases [20].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…7% of dermoid cysts occur in the head and neck, while 1.6% occurs in the mouth [15]. There is no significant gender predilection however a review of literature by Vélez-Crus, et al noted a high incidence among men after 30 years (84.61%) and only 15.38% among women [19]. A higher male predominance (3:1) was also noted by Longo, et al in his review of 16 dermoid cyst cases [20].…”
Section: Discussionmentioning
confidence: 90%
“…Secondly, salivary contamination and infection has been described as risk factors for intraoral incisions. The literature reports an intraoral approach predominance (59.3%) versus (30.5%) for an extraoral approach in the review by Vélez Cruz, et al A mixed approach was only reported in 2 of the 58 cases described [19].…”
Section: Histopathologymentioning
confidence: 97%
See 1 more Smart Citation
“…O cisto dermoide é uma condição rara, a qual recebe esse nome pois possui um epitélio semelhante à epiderme contendo estruturas anexas a sua parede características da pele, tais como glândulas sebáceas, sudoríparas, folículos pilosos e unhas. Segundo a Organização Mundial da Saúde, o cisto dermóide é uma neoplasia de células germinativas, benigna, de crescimento lento e progressivo [1][2][3][4][5][6][7] . Essa lesão é mais comum em crianças e adultos jovens, não tendo predileção por sexo ou raça 1,3,4,5,8 .…”
Section: Introductionunclassified
“…Segundo a Organização Mundial da Saúde, o cisto dermóide é uma neoplasia de células germinativas, benigna, de crescimento lento e progressivo [1][2][3][4][5][6][7] . Essa lesão é mais comum em crianças e adultos jovens, não tendo predileção por sexo ou raça 1,3,4,5,8 . São comumente localizados em região de linha média de assoalho bucal quando ocorrem em cavidade oral, podendo também ser encontrados em língua, dorso nasal, palato mole e duro, parede faríngea lateral e em região labial 1,3,4,5,8,9 .…”
Section: Introductionunclassified